Aluminum alloy clad material

By optimizing the composition and process of aluminum alloy sandwich material, the problem of difficult to take into account both high strength and moldability is solved, and aluminium alloy sandwich material with high strength and excellent moldability is achieved, which is suitable for product manufacturing in complex shapes.

JP2025014983AActive Publication Date: 2025-01-30MA ALUMINUM CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023118008
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-20
Publication Date
2025-01-30
Estimated Expiration
2043-07-20

AI Technical Summary

Technical Problem

The existing aluminum alloy sandwich materials are difficult to balance between high strength and moldability, especially during the casting process, which easily generates large metal compounds, affecting the distribution density and durability of the material, resulting in poor moldability and difficult to control shape.

Method used

By optimizing the composition ratio of aluminum alloy interlayer materials, controlling the distribution density and particle size of metal compounds, limiting the number of compounds greater than 200μm, and inhibiting the generation of large compounds through specific casting and heat treatment processes, combining different layers of aluminum alloy material stacking design to improve overall strength and moldability.

Benefits of technology

The aluminum alloy sandwich material that achieves high strength and excellent moldability can effectively inhibit the formation of large metal compounds during the casting process, improve the durability and moldability of the material, and is suitable for product manufacturing in complex shapes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025014983000001
    Figure 2025014983000001
  • Figure 2025014983000002
    Figure 2025014983000002
  • Figure 2025014983000003
    Figure 2025014983000003
Patent Text Reader

Abstract

To provide an aluminum alloy clad material which is excellent in intensity and molding ability, by suppressing generation of giant intermetallic compounds.SOLUTION: An aluminum alloy clad material comprises in mass%: 0.7 to 1.7% of Mn; 0.5 to 1.7% of Si; 0.1 to 1.2% of Cu; 0.2 to 0.8% of Fe; 0.05 to 1.1% of Zn, and includes, as a residue, Al and inevitable impurities. A component content in the composition satisfies a relation expression of [%Mn]+[%Fe]+|(1-[%Si]) / [%Si]|≤2.6. In the composition, distribution density of distributed particles having sizes of 100 nm to 500 nm is distributed in 1.0×106 to 5.0×106 per 1 mm2, and compounds having a diameter of 200 μm or more is distributed by one piece or lower in 10 mm2. On the aluminum alloy clad material, a skin material formed of a sacrificial material or brazing filler metal is laminated. In the aluminum alloy clad material, tensile strength is 150 MPa to 250 MPa, and an average value rave calculated on the basis of an r value measured from directions of 0°, 45°, 90°to a rolling direction is 0.6 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aluminum alloy clad material having high strength and excellent formability. [Background technology]

[0002] It is known that aluminum alloy clad materials used in heat exchangers contain Mn, Si, Cu, and Fe in the core material to increase strength. For example, Patent Document 1 provides an aluminum alloy brazing sheet for heat exchangers that contains appropriate amounts of Si, Mn, and Fe, and is said to have high strength, excellent corrosion resistance, and bending fatigue properties. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2006-152325 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, it is known that when the core material of an aluminum alloy clad material contains a large amount of Mn, Si, Cu, or Fe, a large amount of giant intermetallic compounds (e.g., 200 μm or more in diameter) are generated during casting. When a large amount of these compounds are generated, the distribution density of the fine dispersed particles decreases, and the strengthening function of the material decreases. In addition, the presence of giant intermetallic compounds can reduce durability by acting as the starting point of fracture, and also deteriorate formability because cracks and fissures can occur from the compounds during forming. For use as a wrought material, it is desirable to produce it in such a way that the formation of large intermetallic compounds is prevented from occurring from the viewpoints of the components and manufacturing process. In addition, when a large amount of elements is added to increase the strength, the elongation generally decreases and the anisotropy of the sheet material increases, which reduces formability and makes it difficult to obtain products with the desired shape. For this reason, it is considered difficult to achieve both high strength and formability in a sheet material. The present invention has been made in light of the above circumstances, and has an object to provide an aluminum alloy clad material in which the formation of large intermetallic compounds is suppressed, and which has high strength and excellent formability. [Means for solving the problem]

[0005] That is, the first embodiment of the aluminum alloy of the present invention is as follows: An aluminum alloy clad material in which one or more skin materials made of a brazing material or a sacrificial material are laminated on one or both sides of a core material made of an aluminum alloy, The core material comprises, in mass%, Mn: 0.7-1.7%, Si: 0.5-1.7%, Cu: 0.1-1.2%, Fe: 0.1-0.8%, Zn: 0.05-1.1%, The remainder is composed of Al and unavoidable impurities, The component contents in the composition satisfy the relational expression [%Mn] + [%Fe] + | (1 - [%Si]) / [%Si] | ≦ 2.6, The distribution density of dispersed particles of 100nm to 500nm is 1mm 2 1.0×10 per 6 pieces~5.0×10 6 The particles are distributed in small particles, and the particles with a diameter of 200 μm or more are within 10 mm. 2 are distributed at less than one per The aluminum alloy clad material has a tensile strength of 150 MPa to 250 MPa, and an average r value calculated from r values ​​measured in the directions of 0°, 45°, and 90° to the rolling direction. ave is 0.6 or more.

[0006] Another aspect of the invention of the aluminum alloy is the above-mentioned aspect of the invention, The composition of the core material further comprises: In mass%, Cr: 0.01 to 0.30%, Zr: 0.01 to 0.30%, Ti: 0.01 to 0.30%, and Mg: 0.1-1.2%, Contains one or more of the following.

[0007] In another embodiment of the aluminum alloy of the present invention, in the above-mentioned embodiment, a brazing material as the skin material is laminated on one or both sides of the core material in the order of brazing material / core material.

[0008] In another embodiment of the aluminum alloy of the present invention, in the above-described embodiment, a brazing material and a sacrificial material as the skin materials are laminated on both sides of the core material in the order of brazing material / core material / sacrificial material.

[0009] Another aspect of the invention of the aluminum alloy is the above-mentioned aspect of the invention, The brazing material as the skin material is In mass%, Si: 2.0 to 13.0%; Fe: 0.8% or less, Zn: 5.0% or less, Cu: 1.0% or less, Mn: 2.0% or less, Cr: 0.50% or less, Zr: 0.30% or less, Ti: 0.30% or less, Ni: 1.5% or less, Mg: 2.0% or less, Sr: 0.2% or less, Na: 0.2% or less, V: 0.2% or less, Bi: 1.0% or less, Sb: 1.0% or less, and Sn: Contains one or more elements in an amount of 1.0% or less, with the remainder being Al and unavoidable impurities.

[0010] Another aspect of the invention of the aluminum alloy is the above-mentioned aspect of the invention, The sacrificial material as the skin material is In mass%, Si: 1.5% or less, Fe: 0.8% or less, Zn: 0.4-10.0% Cu: 1.0% or less, Mn: 2.0% or less, Cr: 0.50% or less, Zr: 0.30% or less, Ti: 0.30% or less, Ni: 1.5% or less, Mg: 3.0% or less, Sr: 0.2% or less, Na: 0.2% or less, V: 0.2% or less, Bi: 1.0% or less, Sb: 1.0% or less, and Sn: 1.0% or less, The remainder is composed of Al and unavoidable impurities.

[0011] The reasons for specifying the composition components and the like in the present invention will be explained below.

[0012] (Heartwood composition) The formation of giant intermetallic compounds is suppressed by optimizing the balance of each element added. The following contents are all shown in mass%.

[0013] Mn: 0.7-1.7% The inclusion of Mn improves material strength through solid solution strengthening and precipitation as intermetallic compounds such as Al-Mn, Al-Mn-Si, Al-Mn-Fe, and Al-Mn-Fe-Si. If the Mn content is too low, the desired strength improvement effect cannot be obtained. On the other hand, if the content is excessive, giant intermetallic compounds are formed during casting, reducing manufacturability. For this reason, the lower limit of the Mn content is set at 0.7% and the upper limit at 1.7%. For similar reasons, it is desirable to set the upper limit at 1.5% and the lower limit at 0.8%.

[0014] Silicon: 0.5 to 1.7% The inclusion of Si improves the strength of the material through solid solution strengthening and dispersion strengthening caused by precipitation of Si as intermetallic compounds such as Al-Mn-Si and Al-Mn-Fe-Si. If the Si content is too low, the desired strength improvement effect cannot be obtained. On the other hand, if the content is too high, huge intermetallic compounds are generated during casting, which reduces manufacturability. For this reason, the lower limit of the Si content is set to 0.5% and the upper limit is set to 1.7%. For similar reasons, it is desirable to set the upper limit at 1.6% and the lower limit at 0.6%.

[0015] Cu: 0.1-1.2% The inclusion of Cu improves material strength through solid solution strengthening. In addition, adding Cu together with Zn improves elongation and contributes to improving formability. If the Cu content is too low, the desired strength improvement effect cannot be obtained. On the other hand, if the content is excessive, cracks are likely to occur during casting. For this reason, the lower limit of the Cu content is set at 0.1% and the upper limit at 1.2%. For the same reasons, it is desirable to set the upper limit at 0.9% and the lower limit at 0.15%.

[0016] Fe: 0.1-0.8% The inclusion of Fe causes it to precipitate as intermetallic compounds, mainly Al-Fe, Al-Fe-Si, Al-Mn-Fe, and Al-Mn-Fe-Si, improving the strength of the material. Fe is present as an impurity in the raw materials, so if it is contained below the lower limit, it will be costly. In addition, the desired strength improvement effect will not be obtained. On the other hand, if it is contained in excess, huge intermetallic compounds will be generated during casting, reducing manufacturability. For this reason, the lower limit of the Fe content is set at 0.1% and the upper limit at 0.8%. For the same reasons, it is preferable to set the upper limit at 0.65% and the lower limit at 0.20%, and more preferably the lower limit at 0.25%.

[0017] Zn: 0.05-1.1% The inclusion of Zn improves strength and formability by refining crystal grains. In addition, adding it together with Cu improves elongation and formability. If the content is below the lower limit, the desired effect cannot be obtained. On the other hand, if the content is excessive, the effect on formability is small, but the self-corrosion rate increases, decreasing corrosion resistance. For this reason, it is preferable to set the lower limit of the Zn content at 0.05% and the upper limit at 1.1%. For the same reasons, it is desirable to set the upper limit at 1.0% and the lower limit at 0.35%.

[0018] Ti, Zr, Cr: 0.01 to 0.30% These components improve the strength of the material by solid solution strengthening and dispersion strengthening due to precipitation as intermetallic compounds, so one or more of them may be contained as desired. If the content of these elements is too low, the desired strength improvement effect cannot be obtained. On the other hand, if the content is too high, huge intermetallic compounds are generated during casting, reducing manufacturability. For this reason, the lower limit of the content of these elements is set to 0.01% and the upper limit is set to 0.30%. For the same reason, it is preferable to set the upper limit of the Ti and Zr contents at 0.1% and the lower limit at 0.05%. The upper limit of the Cr content is preferably 0.08% and the lower limit is preferably 0.05%. Even if these elements are not added, any of the elements may be contained as unavoidable impurities, and in that case, each of them is preferably less than 0.01%.

[0019] Mg: 0.1-1.2% The inclusion of Mg improves the strength of the material by providing solid solution strengthening and aging precipitation ability as an Mg--Si based intermetallic compound, and therefore Mg is added as desired. If the Mg content is too low, the desired strength improvement effect cannot be obtained. On the other hand, if the Mg content is excessive, cracks are likely to occur during hot rolling, and manufacturability is reduced. Therefore, when Mg is contained, the lower limit is set to 0.1% and the upper limit is set to 1.2%. For the same reasons, it is desirable to set the upper limit at 1.0% and the lower limit at 0.4%. Even when Mg is not added, Mg may be contained as an unavoidable impurity, in which case the content is preferably 0.05% or less.

[0020] Component content [%Mn]+[%Fe]+|(1-[%Si]) / [%Si]|≦2.6 By satisfying these relations, the formation of giant intermetallic compounds is suppressed. If these relations are not satisfied, it becomes difficult to suppress the formation of giant intermetallic compounds, regardless of the conditions of the production method and the like. The above formula was obtained by performing a regression analysis of the relationship between the component content and the number of compounds with a diameter of 200 μm or more per unit area, and the correspondence between the number of compounds with a diameter of 200 μm or more present in the manufactured alloy and the amounts of Mn, Fe, and Si added. By satisfying the above formula, it is possible to suppress the number of compounds with a diameter of 200 μm or more to within 10 mm 2 If the above relation is not satisfied, the number of giant compounds generated will be 1 or less per 10 mm. 2 It becomes difficult to achieve less than one per prize.

[0021] (Heartwood characteristics) The distribution density of dispersed particles of 100nm to 500nm is 1mm 2 1.0×10 per 6 pieces~5.0×10 6 pieces In order to obtain the desired tensile strength after annealing, it is necessary to adjust the distribution state of the intermetallic compounds as described above. Since the desired strength cannot be obtained if the particle size of the intermetallic compounds is less than 100 nm or more than 500 nm, we focused on dispersed particles of 100 nm to 500 nm. The dispersion density of these dispersed particles is 1.0 × 10 6 Less than 5.0 x 10 6 If the number exceeds 1, the desired strength cannot be obtained.

[0022] Compounds over 200μm are 10mm 2 1 or less If these compounds are present, they may cause surface peeling or breakage during rolling, resulting in reduced rollability. In addition, these large compounds may act as starting points for fracture during part molding or product specification.

[0023] (Clad material characteristics) Tensile strength: 150MPa~250MPa After annealing, the tensile strength is preferably in the above range. If the strength is less than 150 MPa, the structural strength after forming cannot be maintained. On the other hand, if the tensile strength is more than 250 MPa, cracks may occur during forming.

[0024] The average value r calculated from the r values ​​(Lankford values) measured at 0°, 45°, and 90° to the rolling direction ave is 0.6 or more The r value is preferably 0.6 or more. ave is measured at room temperature and calculated using the following formula based on the r-values ​​(r0°, r45°, r90°) measured at 0.5% strain less than the strain (uniform elongation) at which the tensile strength is obtained. r ave =(r0°+r90°+2*r45°) / 4 r ave If it is less than 0.6, the anisotropy becomes high, the press formability decreases, and cracks and the like tend to occur.

[0025] (Layer structure of clad material) The clad material has one or more skin materials, which are skin materials or sacrificial materials, laminated on one or both sides of the core material. The cladding ratio of each layer of the cladding material is not particularly limited, but it is preferable that the cladding ratio of the core material is in the range of 60 to 97%. The skin material is selected from a brazing material and a sacrificial material. The lamination structure is not particularly limited, but examples thereof include an aluminum alloy clad material laminated in the order of brazing material / core material, an aluminum alloy clad material laminated in the order of brazing material / core material / brazing material, an aluminum alloy clad material laminated in the order of brazing material / core material / sacrificial material, an aluminum alloy clad material laminated in the order of brazing material / core material / sacrificial material / brazing material, an aluminum alloy clad material laminated in the order of brazing material / sacrificial material / core material / sacrificial material / brazing material, an aluminum alloy clad material laminated in the order of sacrificial material / core material, an aluminum alloy clad material laminated in the order of sacrificial material / core material, and an aluminum alloy clad material laminated in the order of sacrificial material / core material.

[0026] Brazing material type The core material can be made of Al-Si alloys, which are common brazing materials for skin materials, and brazing materials containing various elements. The brazing material does not contribute much to the overall strength of the clad material, but if the brazing material contains an element that has a particularly large effect on improving strength, the strength of the clad material as a whole can be adjusted by taking into account its influence.

[0027] The strength of the entire clad material can be calculated by dividing the strength of each layer by the clad ratio as shown in the formula below. Overall strength of clad material = (strength of skin material alone x skin clad ratio) + (strength of core material alone x core clad ratio)

[0028] Furthermore, among the elements optionally contained in the brazing filler metal, Mg, Mn, Cu, and Fe can be cited as elements that easily contribute to the strength of the brazing filler metal alone. The effect of each on the strength of the brazing filler metal alone is as follows: [Tensile strength] Contains Mg: 5MPa / 0.1%, Mn: 2MPa / 0.1%, Cu: 5MPa / 0.1%, Fe: 2MPa / 0.1%.

[0029] On the other hand, the formability of the entire clad material is such that the formability of the skin material is greater than that of the core material, and is therefore fundamentally determined by the formability of the core material, i.e., its chemical composition and metal structure.

[0030] (Brazing composition) The components contained in the brazing material are not limited to specific ones, but the following are typical examples of the components.

[0031] Si: 2.0-13.0% It lowers the melting point and produces a liquid phase at the brazing temperature, making brazing possible. Below the lower limit, the amount of liquid phase generated is small, resulting in poor brazing. Above the upper limit, erosion occurs due to excess Si.

[0032] Fe: 0.8% or less It may be contained (it may be 0%). If the upper limit is exceeded, a large compound is generated, making production difficult.

[0033] Zn: 5.0% or less May be contained (may be 0%). Contains when it is desired for the brazing filler metal to function as a corrosion protection layer for the core material. When contained, the potential becomes less noble and acts as a sacrificial anode for the core material. If the upper limit is exceeded, the corrosion rate becomes too fast.

[0034] Cu: 1.0% or less It may be contained (it may be 0%). If the content exceeds the upper limit, the material becomes hard and manufacturing becomes difficult.

[0035] Mn: 2.0% or less It may be contained (it may be 0%). If the upper limit is exceeded, a large compound is generated, making production difficult.

[0036] Cr:0.50% or less It may be contained (it may be 0%). If the upper limit is exceeded, a large compound is generated, making production difficult.

[0037] Zr: 0.30% or less It may be contained (it may be 0%). If the upper limit is exceeded, a large compound is generated, making production difficult.

[0038] Ti: 0.30% or less It may be contained (it may be 0%). If the upper limit is exceeded, a large compound is generated, making production difficult.

[0039] Ni: 1.5% or less It may be contained (it may be 0%). If the upper limit is exceeded, a large compound is generated, making production difficult.

[0040] Mg: 2.0% or less May be contained (may be 0%). Contains when used for vacuum brazing, etc. If the content exceeds the upper limit, the material becomes hard and manufacturing becomes difficult.

[0041] Sr: 0.2% or less It may be contained (it may be 0%).

[0042] Na: 0.2% or less It may be contained (it may be 0%).

[0043] V: 0.2% or less It may be contained (it may be 0%).

[0044] Bi: 1.0% or less It may be contained (it may be 0%).

[0045] Sb: 1.0% or less It may be contained (it may be 0%).

[0046] Sn: 1.0% or less It may be contained (it may be 0%).

[0047] (Sacrificial material composition) The core material may be clad with a sacrificial material having a lower electrical potential than the core material as a skin material. In addition to the common sacrificial material Al-Zn alloy, sacrificial materials containing various elements can be bonded to the clad material. Although the contribution of the sacrificial material to the overall strength of the clad material is small, when the sacrificial material contains an element that has a particularly large effect on improving strength, the strength of the entire clad material can be adjusted by taking into account its influence.

[0048] The strength of the entire clad material can be calculated by dividing the strength of each layer by the clad ratio as shown in the formula below. Overall strength of clad material = (strength of skin material alone x skin clad ratio) + (strength of core material alone x core clad ratio)

[0049] Furthermore, among the elements optionally contained in the sacrificial material, Mg, Mn, Si, Cu, and Fe can be listed as elements that easily contribute to the strength of the sacrificial material alone. The effect of each on the strength of the sacrificial material alone is as follows: [Tensile strength] Contains Mg: 5MPa / 0.1%, Mn: 2MPa / 0.1%, Si: 5MPa / 0.1%, Cu: 5MPa / 0.1%, Fe: 2MPa / 0.1%.

[0050] The formability of the entire clad material, like that of the brazing material, is such that the formability of the skin material is greater than that of the core material, and is therefore fundamentally determined by the formability of the core material, i.e., its chemical composition and metal structure.

[0051] (Sacrificial material composition) The components contained in the sacrificial material are not limited to any particular ones, but the following are typical examples of the components.

[0052] Si: 1.5% or less It may be contained (it may be 0%). If the upper limit is exceeded, the melting point is lowered and local melting occurs.

[0053] Fe: 0.8% or less It may be contained (it may be 0%).

[0054] Zn: 0.4-10.0% May be contained (may be 0%). It is contained to make the potential baser and obtain a sacrificial anode effect on the core material. Below the lower limit, the effect is small, while above the upper limit, the corrosion rate becomes too fast and the sacrificial material is quickly consumed, preventing the sacrificial anode effect from being exerted for a long period of time.

[0055] Cu: 1.0% or less It may be contained (it may be 0%). If the content exceeds the upper limit, the material becomes hard and manufacturing becomes difficult.

[0056] Mn: 2.0% or less It may be contained (it may be 0%). If the upper limit is exceeded, a large compound is generated, making production difficult.

[0057] Cr:0.50% or less It may be contained (it may be 0%). If the upper limit is exceeded, a large compound is generated, making production difficult.

[0058] Zr: 0.30% or less It may be contained (it may be 0%). If the upper limit is exceeded, a large compound is generated, making production difficult.

[0059] Ti: 0.30% or less It may be contained (it may be 0%). If the upper limit is exceeded, a large compound is generated, making production difficult.

[0060] Ni: 1.5% or less It may be contained (it may be 0%). If the upper limit is exceeded, a large compound is generated, making production difficult.

[0061] Mg: 3.0% or less May be contained (may be 0%). Contains when used for vacuum brazing, etc. If the content exceeds the upper limit, the material becomes hard and manufacturing becomes difficult.

[0062] Sr: 0.2% or less It may be contained (it may be 0%).

[0063] Na: 0.2% or less It may be contained (it may be 0%).

[0064] V: 0.2% or less It may be contained (it may be 0%).

[0065] Bi: 1.0% or less It may be contained (it may be 0%).

[0066] Sb: 1.0% or less It may be contained (it may be 0%).

[0067] Sn: 1.0% or less It may be contained (it may be 0%). Effect of the Invention

[0068] According to the present invention, a clad material having high strength and excellent formability can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0069] [Creating core material] [Heart composition] The aluminum alloy for the core material is prepared to contain, by mass%, Mn: 0.7-1.7%, Si: 0.5-1.7%, Cu: 0.1-1.2%, Fe: 0.1-0.8%, Zn: 0.05-1.1%, and optionally one or more of Cr: 0.01-0.30%, Zr: 0.01-0.30%, Ti: 0.01-0.30%, Mg: 0.1-1.2%, with the remainder being Al and unavoidable impurities. At this time, the component contents of the composition are prepared to satisfy the relational expression: [%Mn]+[%Fe]+|(1-[%Si]) / [%Si]|≦2.6.

[0070] [casting] The aluminum alloy having the above composition is produced by melting, for example, by semi-continuous casting. When casting is performed at a normal casting speed, Al-Mn-Fe compounds grow between the start of casting and solidification, making it easy for giant intermetallic compounds of 200 μm or more to form. To prevent this, it is desirable to cool the alloy at a cooling rate of 0.1°C / s to 10°C / s when passing through 640°C to 670°C during casting. This effectively prevents the formation of giant intermetallic compounds of 200 μm or more. 640°C to 670°C is the temperature at which the above compounds grow. If the cooling rate is less than 0.1°C / sec, giant intermetallic compounds are likely to be generated. If the cooling rate is 10°C / sec or more, the generation of giant intermetallic compounds is effectively suppressed, but the cracking sensitivity increases and manufacturability decreases. More preferably, the cooling rate in the above temperature range is 0.5°C / sec to 5°C / sec.

[0071] [Homogenization process] The resulting alloy may be subjected to a homogenization treatment. In the homogenization treatment, the obtained alloy can be subjected to a homogenization treatment at a temperature of 400°C to less than 600°C and for a treatment time of 3 to less than 12 hours. This provides a finely dispersed state of intermetallic compounds with a circle equivalent diameter of about 100 nm to 500 nm, which is suitable for obtaining desired properties. If conditions other than the above temperature and treatment time are used, the desired distribution state of intermetallic compounds cannot be obtained, and the strength decreases. In addition, at 600°C or higher, there is a risk that the material will melt during the homogenization treatment. A more preferable temperature is 420°C to 580°C.

[0072] "Hot rolling" Separately, the brazing alloy and the sacrificial alloy are cast and hot rolled to a predetermined thickness by a conventional method, and then laminated with a core ingot and hot rolled to produce a clad material. The brazing alloy contains, by mass%, 2.0 to 13.0% Si, and further contains Fe: 0.8% or less, Zn: 5.0% or less, Cu: 1.0% or less, Mn: 2.0% or less, Examples of compositions include Cr: 0.50% or less, Zr: 0.30% or less, Ti: 0.30% or less, Ni: 1.5% or less, Mg: 2.0% or less, Sr: 0.2% or less, Na: 0.2% or less, V: 0.2% or less, Bi: 1.0% or less, Sb: 1.0% or less, Sn: 1.0% or less, and the remainder being Al and unavoidable impurities. Each component other than Si may be 0%. The aluminum alloy for the sacrificial material may be, by mass%, Si: 1.5% or less, Fe: 0.8% or less, Zn: 0.4 to 10.0%, Cu: 1.0% or less, Mn: 2.0% or less, Cr: 0.50% or less, Zr: 0.30% or less, Ti: 0.30% or less, Ni: 1.5% or less, Mg: 3.0% or less, Sr: 0.2% or less, Na: 0.2% or less, V: 0.2% or less, Bi: 1.0% or less, Sb: 1.0% or less, Sn: 1.0% or less, with the remainder being Al and unavoidable impurities. Each component may be 0%.

[0073] Here, it is preferable that the soaking treatment before hot rolling of the clad material is performed at a temperature of 400°C to 550°C for 1 to 10 hours. At a temperature higher than this, the dispersed particles precipitated during the homogenization treatment are redissolved, and the material strength decreases. In addition, in order to crush the giant intermetallic compounds generated during casting during hot rolling, it is preferable to perform 15 or more passes of rolling so that the thickness of the exit side is reduced by 20 mm or more compared to the thickness of the entry side. In addition, by performing this condition, the crushed intermetallic compounds become about 1 μm in size, which effectively acts as a nucleation site, and the distribution state of the intermetallic compounds is optimized, thereby improving the r-value of the plate material. If the reduction amount or number of passes is less than this, the large intermetallic compounds formed during casting remain, and the subsequent manufacturability is reduced. On the other hand, a reduction amount of more than 30 mm is effective in crushing the large intermetallic compounds, but promotes cracks in the plate width direction, which reduces manufacturability. Therefore, it is more preferable to set the reduction amount per pass to 20 mm to 30 mm and the number of passes to 15 or more.

[0074] "Cold rolling" The aluminum alloy clad material that has been hot rolled can be cold rolled. Although not particularly specified, it is preferable to carry out the cold rolling at a rolling reduction rate per pass of 10 to 40%. Outside this range, manufacturability decreases.

[0075] "Annealing during rolling" It may be performed during cold rolling to continue the cold rolling. It can be performed in a batch-type annealing furnace at a temperature increase rate of 30 to 70°C / hour at 200 to 450°C for a treatment time of 3 to 10 hours. If the temperature exceeds 450°C, secondary recrystallization may occur, resulting in non-uniform recrystallized grains. Also, a continuous annealing furnace (heating rate of 50° C. / s or more, treatment temperature of 400° C. or more, treatment time of 60 s, cooling rate of 200° C. / s or less) may be used.

[0076] "Final plate thickness" Although not particularly defined, a range of 0.5 mm to 3.5 mm is exemplified.

[0077] "Annealing" The aluminum alloy clad material after cold rolling can be subjected to final annealing, which can be performed in a batch annealing furnace at a temperature increase rate of 30-70°C / hour to 200-400°C for a treatment time of 3-10 hours. Furthermore, if a continuous annealing furnace (heating rate of 50°C / s or more, treatment temperature of 400°C or more, treatment time of 60 s, cooling rate of 200°C / s or less) is used, the crystal grains after annealing become finer, improving strength and formability. If necessary, final rolling may be further performed in the range of 10 to 40% after annealing. In the above description, final annealing is performed after cold rolling. However, in this embodiment, final annealing is not performed after cold rolling, and the steel sheet can be used in its as-rolled state.

[0078] In the aluminum alloy clad material that has undergone the above process, the distribution density of dispersed particles of 100 nm to 500 nm in the core material is 1 mm 2 1.0×10 per 6 pieces~5.0×10 6 The particles are distributed in small particles, and the particles with a diameter of 200 μm or more are within 10 mm. 2 are distributed at less than one per

[0079] In addition, the aluminum alloy clad material after manufacturing has a tensile strength of 150MPa to 250MPa after annealing or as-rolled, and the average r value calculated from the r values ​​measured in the directions of 0°, 45°, and 90° to the rolling direction. ave has a value of 0.6 or more. The aluminum alloy of the present invention is not limited to a specific application, but can be suitably used, for example, as a plate material for a heat exchanger. EXAMPLES

[0080] The aluminum alloys for the core material (the balance being Al and unavoidable impurities) shown in Table 1 were prepared. The calculated values ​​for the relationship [%Mn] + [%Fe] + |(1-[%Si]) / [%Si]| for each composition are shown in Table 1. The casting method for this alloy was semi-continuous casting, and when the aluminum alloy object temperature passed through 640°C to 670°C, the cooling rate was controlled to a range of 0.5°C to 5.0°C / sec by adjusting the appropriate casting speed and cooling water amount. For cooling rates below 640°C, casting was performed at a general casting speed. In Table 5, those in which the cooling rate was controlled to a range of 0.5°C to 5.0°C / sec in the range of 640°C to 670°C are indicated with ●, and those in which the cooling rate was controlled to less than 0.5°C / sec are indicated with △.

[0081] In addition, the brazing alloys shown in Table 2 and the sacrificial alloys shown in Table 3 were similarly produced by semi-continuous casting. The brazing alloys and the sacrificial alloys were cast under normal conditions. The brazing alloys and the sacrificial alloys were adjusted in thickness by hot rolling to have the clad ratios shown in Table 4, and then combined with the core alloys and hot rolled to produce clad materials.

[0082] The core alloy ingot was homogenized under the conditions shown in Table 5, and then combined with the brazing alloy and the sacrificial alloy as described above, and soaked at 500°C for 1 hour, and then hot rolled. The hot rolling conditions (number of passes when rolling with a reduction of 20 mm to 30 mm) are shown in Table 5. The thickness of the hot rolled material was 8.0 mm, and then cold rolling was performed to obtain a cold rolled material with a plate thickness of 0.8 mm. For test material No. 21, intermediate annealing was performed during cold rolling. After hot rolling, the material was rolled to 3.0 mm by cold rolling, and then heat treatment was performed at 350°C for 4 hours as intermediate annealing conditions. Then, cold rolling was performed to obtain a cold rolled material with a plate thickness of 0.8 mm. After cold rolling to 0.8 mm, final annealing was performed at 350°C for 3 hours (quality grade O material). For some samples (No. 31 and 32), the final annealing was performed just before 0.8 mm, and samples were also prepared in which the thickness was reduced to 0.8 mm in order to achieve the specified cold rolling reduction (15% and 30% final rolling reduction for temper H material, respectively).

[0083] "Distribution of compounds" Identification of compounds over 200 μm in size The cross section of the produced aluminum alloy parallel to the rolling direction was mechanically polished, and the intermetallic compounds were observed under an optical microscope at a magnification of 100x and a 0.35 mm 2 Ten fields of view were observed with an area of ​​10 mm, and from the 10 images obtained, the circle equivalent diameter and distribution amount of the intermetallic compound particles were calculated using image analysis software (e.g., ImageJ, developed by Wayne Rasband). The results are shown in Table 5.

[0084] Confirmation of compounds from 100 to 500 nm As above, a cross-section parallel to the rolling direction was polished with a cross-section polisher, and a secondary electron image was taken at a magnification of 30,000 times and a resolution of 12 μm using a field emission scanning electron microscope (FE-SEM; JEOL Ltd. JSM-7900F). 2 Ten fields of view were observed with an area of ​​10 mm, and 10 images were taken. From the images taken, the circle equivalent diameter and distribution amount of the intermetallic compound particles were calculated using image analysis software, and the results are shown in Table 5.

[0085] [Tensile strength] Tensile Test No. 5 test pieces were taken parallel to the rolling direction in accordance with JIS Z 2241, and the tensile strength was measured. Tensile strength was evaluated as follows: less than 140 MPa x, 140 MPa or more but less than 180 MPa ◯, and 180 MPa or more ◎. The results are shown in Table 5.

[0086] [Average r value] The r-value was measured at a strain of minus 0.5% from the strain (uniform elongation) at which tensile strength was obtained. The measurement method for the r-value was the usual method. The direction parallel to the rolling direction was set as 0°, and r0° was measured. Similarly, r45° from the 45° direction and r90° from the 90° direction were measured. The average r value was calculated as (r0° + r90° + 2*r45°) / 4, and absolute values ​​of 0.6 or greater and less than 0.7 were evaluated as O, values ​​of 0.7 or greater were evaluated as ◎, and values ​​less than 0.6 were evaluated as ×. The calculated values ​​and evaluations are shown in Table 5.

[0087] [Moldability evaluation] To evaluate formability, we carried out press molding, including punching and bending. Parts with particularly excellent dimensional accuracy were rated A, parts that met the standards in other areas were rated B as passing, and parts that were not excellent were rated C as failing. The results are shown in Table 5.

[0088] [Table 1]

[0089] [Table 2]

[0090] [Table 3]

[0091] [Table 4]

[0092] [Table 5]

Claims

1. An aluminum alloy clad material in which one or more skin materials made of a brazing material or a sacrificial material are laminated on one or both sides of a core material made of an aluminum alloy, The core material comprises, in mass %, Mn: 0.7 to 1.7%, Si: 0.5-1.7%, Cu: 0.1-1.2%, Fe: 0.1-0.8%, Zn: 0.05-1.1%, The remainder is composed of Al and unavoidable impurities, The component contents in the composition satisfy the relational expression of [%Mn] + [%Fe] + | (1 - [%Si]) / [%Si] | ≦ 2.6, The distribution density of dispersed particles of 100 nm to 500 nm is 1 mm 2 1.0 x 10 per 6 pieces ~ 5.0×10 6 The particles are distributed in a size of 10 mm or more, and the number of particles larger than 200 μm is 2 are distributed at less than one per The aluminum alloy clad material has a tensile strength of 150 MPa to 250 MPa, and an average r value calculated from r values ​​measured in the directions of 0°, 45°, and 90° with respect to the rolling direction. ave is 0.6 or more; 1. An aluminum alloy clad material comprising:

2. The composition of the core material further comprises: In mass percent, Cr: 0.01-0.30%, Zr: 0.01 to 0.30%, Ti: 0.01 to 0.30%, and Mg: 0.1-1.2%, The aluminum alloy clad material according to claim 1, which contains one or more of the following:

3. 3. The aluminum alloy clad material according to claim 1, wherein the brazing material as the skin material is laminated on one or both sides of the core material in the order brazing material / core material.

4. 3. The aluminum alloy clad material according to claim 1, wherein the brazing material and the sacrificial material as the skin materials are laminated on both sides of the core material in the order of brazing material / core material / sacrificial material.

5. The brazing material as the skin material is In mass percent, Si: 2.0 to 13.0%; Fe: 0.8% or less, Zn: 5.0% or less, Cu: 1.0% or less, Mn: 2.0% or less, Cr: 0.50% or less, Zr: 0.30% or less, Ti: 0.30% or less, Ni: 1.5% or less, Mg: 2.0% or less, Sr: 0.2% or less, Na: 0.2% or less, V: 0.2% or less, Bi: 1.0% or less, Sb: 1.0% or less, and 3. The aluminum alloy clad material according to claim 1, characterized in that it contains at least one of Sn: 1.0% or less, with the remainder being Al and unavoidable impurities.

6. The brazing material as the skin material is In mass percent, Si: 2.0 to 13.0%; Fe: 0.8% or less, Zn: 5.0% or less, Cu: 1.0% or less, Mn: 2.0% or less, Cr: 0.50% or less, Zr: 0.30% or less, Ti: 0.30% or less, Ni: 1.5% or less, Mg: 2.0% or less, Sr: 0.2% or less, Na: 0.2% or less, V: 0.2% or less, Bi: 1.0% or less, Sb: 1.0% or less, and 4. The aluminum alloy clad material according to claim 3, characterized in that it contains one or more of Sn: 1.0% or less, with the remainder being Al and unavoidable impurities.

7. The brazing material as the skin material is In mass percent, Si: 2.0 to 13.0%; Fe: 0.8% or less, Zn: 5.0% or less, Cu: 1.0% or less, Mn: 2.0% or less, Cr: 0.50% or less, Zr: 0.30% or less, Ti: 0.30% or less, Ni: 1.5% or less, Mg: 2.0% or less, Sr: 0.2% or less, Na: 0.2% or less, V: 0.2% or less, Bi: 1.0% or less, Sb: 1.0% or less, and 5. The aluminum alloy clad material according to claim 4, characterized in that it contains at least one of Sn: 1.0% or less, with the remainder being Al and unavoidable impurities.

8. The sacrificial material as the skin material is In mass percent, Si: 1.5% or less, Fe: 0.8% or less, Zn: 0.4-10.0% Cu: 1.0% or less, Mn: 2.0% or less, Cr: 0.50% or less, Zr: 0.30% or less, Ti: 0.30% or less, Ni: 1.5% or less, Mg: 3.0% or less, Sr: 0.2% or less, Na: 0.2% or less, V: 0.2% or less, Bi: 1.0% or less, Sb: 1.0% or less, and Sn: 1.0% or less, The aluminum alloy clad material according to claim 1 or 2, characterized in that it has a composition containing the above and the remainder consisting of Al and unavoidable impurities.

9. The sacrificial material as the skin material is In mass percent, Si: 1.5% or less, Fe: 0.8% or less, Zn: 0.4-10.0% Cu: 1.0% or less, Mn: 2.0% or less, Cr: 0.50% or less, Zr: 0.30% or less, Ti: 0.30% or less, Ni: 1.5% or less, Mg: 3.0% or less, Sr: 0.2% or less, Na: 0.2% or less, V: 0.2% or less, Bi: 1.0% or less, Sb: 1.0% or less, and Sn: 1.0% or less, The aluminum alloy clad material according to claim 4, characterized in that it has a composition containing the above and the remainder consisting of Al and unavoidable impurities.

10. The sacrificial material as the skin material is In mass percent, Si: 1.5% or less, Fe: 0.8% or less, Zn: 0.4-10.0% Cu: 1.0% or less, Mn: 2.0% or less, Cr: 0.50% or less, Zr: 0.30% or less, Ti: 0.30% or less, Ni: 1.5% or less, Mg: 3.0% or less, Sr: 0.2% or less, Na: 0.2% or less, V: 0.2% or less, Bi: 1.0% or less, Sb: 1.0% or less, and Sn: 1.0% or less, The aluminum alloy clad material according to claim 5, characterized in that it has a composition containing the above and the remainder consisting of Al and unavoidable impurities.

Citation Information

Patent Citations

  • Aluminum alloy laminate having excellent fatigue property

    JP2009191293A

  • Aluminum alloy laminate sheet

    JP2015196858A

  • Aluminum alloy laminate sheet

    JP2015196859A

  • Surface-treated aluminum alloy, and surface-treated aluminum alloy clad material

    JP2017082266A

  • Manufacturing method of aluminum alloy and aluminum alloy material

    JP2023116058A